Merging ontologies requires interlocking instituitional worlds - Colomb, Robert Micheal; Ahmad, Mohammad Nazir (IOS Press Amsterdam, The Netherlands, The Netherlands, 2007)

(untitled)
Merging of ontologies is a frequently addressed problem in the ontology literature. This paper argues that in general two even very similar ontologies cannot be merged. Further, where two ontologies can be merged their conceptualizations are special. They are systems of institutional facts which are interlocking. The argument is based on the literature of the federated database problem and on the concepts of speech act and institutional fact.